Optical Measurement of Surface Topography 2011
DOI: 10.1007/978-3-642-12012-1_5
|View full text |Cite
|
Sign up to set email alerts
|

Chromatic Confocal Microscopy

Abstract: Abstract. Chromatic confocal probes are single point optical sensors built around a confocal coaxial setting that use chromatic dispersion and decoding to obtain the surface distance. Such sensors are usually installed on scanning stages of surface texture measuring instruments, roundness instruments or coordinate measuring machines. Chromatic confocal probes can measure on, and through, transparent material, detect several interfaces between materials and, therefore, calculate thickness. The metrological char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 10 publications
0
23
0
1
Order By: Relevance
“…Accordingly, recent research into nanometer scale surface changes of polished human enamel using confocal laser microscopy concluded that optimal characterization of acid mediated surface texture changes requires surface metrology instrumentation with lateral resolution less than 2.5 µm [3]. Chromatic Confocal profilometry is industry standard for optical surface metrology and is specifically recommended by the ISO 25178 international standard for non-contact 3D metrology [4,5]. However, the lateral resolution of chromatic confocal profilometers is limited by the sensor spot diameter varying from up to 24 microns and also by lateral mechanical scanning which introduces measurement noise during the movement of the x,y stage [6].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, recent research into nanometer scale surface changes of polished human enamel using confocal laser microscopy concluded that optimal characterization of acid mediated surface texture changes requires surface metrology instrumentation with lateral resolution less than 2.5 µm [3]. Chromatic Confocal profilometry is industry standard for optical surface metrology and is specifically recommended by the ISO 25178 international standard for non-contact 3D metrology [4,5]. However, the lateral resolution of chromatic confocal profilometers is limited by the sensor spot diameter varying from up to 24 microns and also by lateral mechanical scanning which introduces measurement noise during the movement of the x,y stage [6].…”
Section: Introductionmentioning
confidence: 99%
“…The results of measuring inclusions in stain B, using LCA were puzzling, indicating loss of data. Non‐measured points can result from many causes, such as the surface height being above or below the measuring range, the focal point falling into a “hole,” the slop being too steep, or reflective/absorptive characteristics of the material (Blateyron, ). In case of fungal inclusions the areas of data “voids” corresponded to the shape and location of fungi.…”
Section: Resultsmentioning
confidence: 99%
“…The CCM consists of a chromatic confocal point probe sensor with a 12 mm measuring range mounted vertically (z) above a lateral (x, y) sample translation system. The plate was moved in a raster scan to build up a 2D grid of surface heights measured using the chromatic confocal principle [12].…”
Section: Dimensional Characterisation Of Platementioning
confidence: 99%